2007
DOI: 10.1179/016164107x172220
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture, a promising adjunctive therapy for essential hypertension: a double-blind, randomized, controlled trial

Abstract: Acupuncture seems to offer an additional benefit to the treatment of hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
96
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 23 publications
3
96
1
2
Order By: Relevance
“…Secondly, their participants may have been healthier. The patient sample studied by Yin et al 35 had lower mean baseline BP (135/ 83 mm Hg) and lower mean body mass index 25 relative to SHARP participants. Lastly and perhaps most importantly, Yin et al 35 compared active acupuncture to a noninvasive sham control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, their participants may have been healthier. The patient sample studied by Yin et al 35 had lower mean baseline BP (135/ 83 mm Hg) and lower mean body mass index 25 relative to SHARP participants. Lastly and perhaps most importantly, Yin et al 35 compared active acupuncture to a noninvasive sham control.…”
Section: Discussionmentioning
confidence: 99%
“…35 Yin et al 35 report BP declines of Ϫ14.8/ Ϫ6.9 mm Hg in their active acupuncture group (nϭ15) versus Ϫ4.0/Ϫ1.1 mm Hg in the sham group (nϭ15; PϽ0.05) after 8 weeks of twice-weekly treatments. The study was double blind and used a noninvasive sham treatment for which masking has been validated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of studies that support the use of acupuncture in patients with hypertension. [16][17][18] A study funded by the National Institutes of Health "Stop Hypertension with the Acupuncture Research Program" enrolled 192 participants with untreated hypertension. 19 The study found that active acupuncture treatment, using both doctorselected points and study-assigned points, lowed blood pressure.…”
Section: Discussionmentioning
confidence: 99%